Analisis Tingkat Burnout pada Perawat Rumah Sakit Umum Daerah di Kota Subulussalam - Endang Swariyana Sinamo; Mardaleta Mardaleta; Nabila Hilmy Zhafira (Indonesia Economic Journal, 2026)
This study aims to determine the level of burnout among nurses at the Regional General Hospital (RSUD) of Subulussalam City. Burnout is a condition characterized by emotional exhaustion, depersonalization, and reduced personal accomplishment, often experienced by healthcare workers due to high workloads and psychological pressure in performing their duties. This research employed a quantitative descriptive approach, involving 50 nurses selected through purposive sampling techniques. Data were collected using a questionnaire that had been tested for validity and reliability, with a Cronbach’s Alpha value of 0.897 indicating a reliable instrument. The results revealed that the level of burnout among nurses at RSUD Subulussalam City was in the moderate to high category, with emotional exhaustion being the most dominant component. Contributing factors to burnout include heavy workloads, shift work systems, and the significant responsibility for patient safety. These findings are consistent with the theory of Maslach and Jackson (1981), which states that professions requiring intensive human interaction, such as nursing, are highly prone to burnout. Therefore, it is recommended that the hospital management improve work stress management, provide psychological support, and implement effective supervision to maintain nurses’ mental well-being and enhance the quality of healthcare services.